Pertumbuhan Sargassum sp. dengan Berat Bibit Berbeda pada Budidaya dengan Metode Patok Dasar - Rovi Ratna Sari; Nunik Cokrowati; Nanda Diniarti (Jurnal Airaha, 2021)
This study aimed to determine the effect of different initial seedling weights on the growth of Sargassum sp. cultivated by the off- bottom method. The research method used is an experimental method using a completely randomized design. The treatments in this study consisted of 5 treatments seedling weight with 4 replications, namely A (25 g), B (50 g), C control (100 g), D (150 g), E (100 g), and F (200 g). Data were analyzed using analysis of variance (ANOVA) at a significance level of 5% with a 95% confidence interval and continued with Duncan's test. The results showed that the absolute weight growth of Sargassum sp. for 30 days of cultivation with different initial seedling weights ranging from 306.25 g - 568 g. The specific growth rate of Sargassum sp. ranged from 19.07% – 21.14%. The number of leaves of Sargassum sp. ranged from 2193 - 4214 strands. The number of Sargassum sp. ranged from 2579 – 4224 pieces. This study concluded that different initial seedling weights had a significant effect on the growth of Sargassum sp. The best growth was treatment E, which was 200 g of seedling weight.